2010
DOI: 10.1186/gb-2010-11-7-r73
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequence of the necrotrophic plant pathogen Pythium ultimum reveals original pathogenicity mechanisms and effector repertoire

Abstract: BackgroundPythium ultimum is a ubiquitous oomycete plant pathogen responsible for a variety of diseases on a broad range of crop and ornamental species.ResultsThe P. ultimum genome (42.8 Mb) encodes 15,290 genes and has extensive sequence similarity and synteny with related Phytophthora species, including the potato blight pathogen Phytophthora infestans. Whole transcriptome sequencing revealed expression of 86% of genes, with detectable differential expression of suites of genes under abiotic stress and in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
364
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 358 publications
(379 citation statements)
references
References 161 publications
12
364
0
3
Order By: Relevance
“…These results support the hypothesis of Zerillo et al (2013) and others (Lévesque et al 2010) that globose sporangial Pythium species, including P. irregulare and P. iwayamai, are less effective at degrading suberized roots, leaves and stems than other plant pathogenic oomycetes that produce cutinases; nevertheless, they can penetrate leaves possibly through stomata. irregulare had fewer annotated PL/PE genes than other Pythium and Phytophthora species, and concluded that these species likely did not completely saccharify this complex sugar.…”
Section: Expression Of Pathogenicity-related Protein Transcriptssupporting
confidence: 81%
“…These results support the hypothesis of Zerillo et al (2013) and others (Lévesque et al 2010) that globose sporangial Pythium species, including P. irregulare and P. iwayamai, are less effective at degrading suberized roots, leaves and stems than other plant pathogenic oomycetes that produce cutinases; nevertheless, they can penetrate leaves possibly through stomata. irregulare had fewer annotated PL/PE genes than other Pythium and Phytophthora species, and concluded that these species likely did not completely saccharify this complex sugar.…”
Section: Expression Of Pathogenicity-related Protein Transcriptssupporting
confidence: 81%
“…The genome size, N50 value and GC content were taken from the respective publications (Armbrust et al ., 2004; Bowler et al ., 2008; Cock et al ., 2010; Lévesque et al ., 2010; Lommer et al ., 2012; Tanaka et al ., 2015; Mock et al ., 2017). …”
Section: Methodsmentioning
confidence: 99%
“…This also implies that AvrPm3 a2/f2 is translocated into the plant cell. In the oomycete Pythium ultimum, a YxSL[KR] motif was found to be conserved among effectors specifically and highly expressed during infection (Lévesque et al, 2010), which somewhat resembles the YxC motif found in powdery mildew effectors, including AvrPm3 a2/f2 . One hypothesis is that the YxC motif could be involved in translocation of the effector protein inside the host cell.…”
Section: Identification Of Avrpm3 A2/f2mentioning
confidence: 99%